Feasibility, safety and effectiveness of robot-assisted retroperitoneal partial adrenalectomy with a new robotic surgical system: A prospective clinical study - Dong, Jie; Ji, Ruoyu; Liu, Guanghua; Zhou, Jingmin; Wang, Huizhen; Xu, Weifeng; Ji, Zhigang; Cui, Liang (Frontiers in Surgery, 2023)
Objectives: To evaluate the feasibility, safety and efficacy of the newly developed KD-SR-01® robotic system for retroperitoneal partial adrenalectomy. Subjects and Methods: We prospectively enrolled patients with benign adrenal mass undergoing KD-SR-01® robot-assisted partial adrenalectomy in our institution from November 2020 to May 2022. Surgeries were performed via a retroperitoneal approach using the KD-SR-01® robotic system. The baseline, perioperative and short-term follow-up data were prospectively collected. A descriptive statistical analysis was performed. Results: A total of 23 patients were enrolled, including nine (39.1%) patients with hormone-active tumors. All patients received partial adrenalectomy via the retroperitoneal approach without conversions to other procedures. The median operative time was 86.5 minutes (interquartile range (IQR), 60.0-112.5) and the median estimated blood loss was 50 mL (range, 20-400). Three (13.0%) patients developed Clavien-Dindo grade I-II postoperative complications. The median postoperative stay was 4.0 days (IQR, 3.0-5.0). All surgical margins were negative. The short-term follow-up demonstrated complete or partial clinical and biochemical success as well as absence of imaging recurrence in all patients with hormone-active tumors. Conclusions: Initial results illustrate that the KD-SR-01® robotic system is safe, feasible and effective for the surgical management of benign adrenal tumors.